2012
DOI: 10.1590/s0073-47212012000400004
|View full text |Cite
|
Sign up to set email alerts
|

Comparação quantitativa da comunidade de aves de um fragmento de floresta semidecidual do interior do Estado de São Paulo em intervalo de 30 anos

Abstract: ABSTRACT.A 30-year quantitative comparison of the bird community of a semideciduous forest remnant in the state of São Paulo. Few studies have evaluated long-term changes in avian abundance in forest remnants. To compare both species richness and abundance of the bird community in a forest fragment located in the municipality of Gália, state of São Paulo, southeastern Brazil, we surveyed forest birds using transect counts. We compared our results with a survey conducted 30 years earlier at the same locality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…O fato de, no intervalo de 25 anos, não terem sido detectadas extinções locais entre as espécies florestais surpreende, quando se consideram os dados disponíveis para outros remanescentes monitorados no interior do Estado de São Paulo (Aleixo e Vielliard, 1995;Willis e Oniki, 2002;Antunes, 2005;Cavarzere et al, 2012). A Fazenda Santa Carlota retém populações de algumas espécies já extintas em fragmentos florestais da região ou em declínio nesses remanescentes, tais como o chocão-carijó (Hypoedaleus guttatus) e o guaxe (Cacicus haemorrhous).…”
Section: Resultsunclassified
“…O fato de, no intervalo de 25 anos, não terem sido detectadas extinções locais entre as espécies florestais surpreende, quando se consideram os dados disponíveis para outros remanescentes monitorados no interior do Estado de São Paulo (Aleixo e Vielliard, 1995;Willis e Oniki, 2002;Antunes, 2005;Cavarzere et al, 2012). A Fazenda Santa Carlota retém populações de algumas espécies já extintas em fragmentos florestais da região ou em declínio nesses remanescentes, tais como o chocão-carijó (Hypoedaleus guttatus) e o guaxe (Cacicus haemorrhous).…”
Section: Resultsunclassified
“…Kirika, Farwig, and Böhning-Gaese (2008) demonstrated that environmental disturbances significantly reduced frugivorous richness and functional variation, affecting mainly specialist birds. In disturbed habitats such as those in which this experiment was conducted, generalist, opportunistic, and edge-tolerant species are favoured and may be able to forage in forest edges, as well as in its interior (Cavarzere, Marcondes, Moraes, & Donatelli, 2012), compensating for the loss of disturbance-sensitive species (Menezes et al, 2016). Thus, generalist birds may still overexploit some fruits colours that are predominant in the community (i.e.…”
Section: Coloursmentioning
confidence: 99%
“…Rapid deforestation for agriculture has been a major agent of land‐use change, especially in southern Brazil, which experienced rapid economic development during the 20th century (Dean 1997, Ribeiro et al 2009, Cardim 2018). The broad reduction in forest area had an overwhelming influence on bird communities, which led to the local extinction of several species and the creation of small and isolated forest remnants, mainly composed of common and generalist birds (Cavarzere et al 2012, 2012, Alexandrino et al 2017). Many of the Anthropocene impacts upon the biota are associated to trophic cascade effects and generate disturbances on the structure of trophic chains as a whole (Magioli et al 2019).…”
Section: Introductionmentioning
confidence: 99%